God wants me to forgive them!?! - Hullfish, Steve; Anderson, Dan, 1954-; Landis, Heidi; Nawrocki, Michael; Power, Bridget; Vischer, Phil.; Vischer, Lisa.; Freeman, Gail.; Morrow, Jeffrey; Olsen, Chris; Ellis, Robert; Heinecke, Kurt.; et al. ([S.l.] : Big Idea Productions ; Burbank, CA : Distributed by Warner Home Video, 2004)
Two fully animated stories that teach children a Biblical perspective on forgiveness. In "The grapes of wrath," what do you do when a bunch of very cranky grapes make fun of five-year old Jr. Asparagus? Can Jr.'s dad show the grapes the error of their ways? Will Jr. ever be able to forgive them? In "Larry's lagoon, " a three hour boat tour takes a turn for the worst when first mate Larry absentmindedly crashes into an uncharted tropical island! Can Skipper Bob and the passengers possibly forgive Larry for making such a huge blunder?
Grapes of wrath -- Larry's lagoon.
DVD, region 1, full screen presentation; Dolby Ditital 5.1 surround sound.
"A lesson in forgiveness"--Container.
Voices: Dan Anderson, Heidi Landis, Mike Nawrocki, Bridget Power, Phil Vischer, Lisa Vischer, Gail Freeman, Jeff Morrow.
Created by Phil Vischer and Michael Nawrocki ; animation director, Chris Olsen ; animators, Robert Ellis ... [et al.] ; editor, Mike Nawrocki ; music, Kurt Heinecke.
MPAA rating: Not rated; for ages 3 through 8.
Bonus features: games and activities; behind the scenes; how to draw; Veggie karaoke, Concept art, Word find game, Audio Commentary, Interactive Storybook, Easter Egg hidden features, Eight chapter selects of favorite scenes, and Dolby digital 5.1 surround sound.
Keywords: Forgiveness -- Religious aspects -- Juvenile drama; Christian life -- Juvenile drama; Religious; Christian life -- Drama; Forgiveness -- Drama; Video recordings for the hearing impaired; Television programs; Animated television programs; Children's television programs